On exact estimates of the order of approximation of functions of several variables in the anisotropic Lorentz–Zygmund space - Gabdolla Akishev (KOMUNITAS Analisis Matematika INDONESIA, 2025)
In this paper we consider L_p, α, τ^*(T^m) anisotropic Lorentz-Zygmund space 2π of periodic functions of m variables and Nikol'skii–Besov's class S_p, α, τ, θ^rB. In this paper, we establish order-sharp estimates of the best approximation by trigonometric polynomials with harmonic numbers from the step hyperbolic cross of functions from the Nikol'skii –Besov class in the norm of the anisotropic Lorentz–Zygmund space.